1985
DOI: 10.1016/0272-7757(85)90003-2
|View full text |Cite
|
Sign up to set email alerts
|

Michigan's experiences with the federal education block grant

Abstract: The results of il dct;lilcd study undcrtahcn in Michigan to dctcrminc the impxt of the Chapter 2 block grant in it> first two yxrs 01 implemcnt;ition. IWQ-198.3 ;md 198.L 198-l. ;1rc summarized in this ;Irticlc. Following ;t discussion of ch;mgcs in intcrgovcrnmcnt;lI rckltionships th;kt resulted lrom Ch;ytcr 2. m;lior ht;ltc dcckion~ ;lnd xtions that ccntercd on the hloch gr;mt progr;lm ilrc dcscrihed. Gener;ll ;md spccillc imprekon~ of the impact of Chapter 2. h;wd on ;,n in-depth study 01 nine public xhool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…What is more, these shifts were along the lines predicted by ACIR (1979) and by Vogel (1979), and in keeping with prior findings of the eight-state study reported by Kyle (1983) and the case study research in Michigan conducted by Kearney (1983Kearney ( , 1985. In Michigan, the block grant had the effect of reallocating federal dollars away from the 13 districts that in prior years had competed successfully for ESAA funds.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…What is more, these shifts were along the lines predicted by ACIR (1979) and by Vogel (1979), and in keeping with prior findings of the eight-state study reported by Kyle (1983) and the case study research in Michigan conducted by Kearney (1983Kearney ( , 1985. In Michigan, the block grant had the effect of reallocating federal dollars away from the 13 districts that in prior years had competed successfully for ESAA funds.…”
Section: Discussionsupporting
confidence: 82%
“…The contention was that it became possible to move to a lower level of funding, without a concurrent lessening of services, because of the increased economies and efficiencies attained under the block grant mechanism. However, in the face of the evidence gathered on the type and level of services provided in the first year of the block grant, this argument lacks validity (Kearney, 1983(Kearney, , 1985Kyle, 1983). But the answer is not so simple.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The second year of the program also showed that districts purchased computers, but the focus of the program was expanded. In Michigan, Kearney (1984) reported districts had not "rushed" out to buy computers. Those districts that did invest in computers were doing so as a part of an overall strategy or plan that was carefully laid out.…”
Section: State and Local Educational Agencies' Responsibilitiesmentioning
confidence: 99%